The Function of MicroRNAs in B-Cell Development, Lymphoma, and Their Potential in Clinical Practice - Zheng, Bing; Xi, Zhijiang; Liu, Rong; Yin, Wei; Sui, Zhiwei; Ren, Boxu; Miller, Heather; Gong, Quan; Liu, Chaohong (Frontiers in Immunology, 2018)
B cell formation, development, and differentiation are complex processes regulated by several mechanisms. Recently, there has been growing evidence indicating that microRNAs are important for normal B cell lineage development. MicroRNAs (miRNAs) are small non-coding RNA molecules, about 20-22 nucleotide in length, that play an important role in regulating gene expression. They pair with specific messenger RNAs (mRNAs), resulting in mRNAs translational repression or degradation. Here, we review current research about the function of miRNAs in the aspects of B-cell physiology and pathology. We start by introducing the process of miRNA biogenesis. We will then focus on the role of miRNAs during B cell lineage commitment and development in the bone marrow, followed by a discussion of miRNAs’ role in subsequent peripheral B cell activation, proliferation, and final differentiation (including B cell central tolerance and autoimmunity). We list and describe several examples to illustrate miRNAs’ role in the development of B-cell lymphoma, both as oncogenes and tumor suppressor genes. Finally, we delineate the potential value of miRNAs in diagnosing B cell lymphoma, predicting clinical outcomes, and modulating the efficiency of anticancer treatments. Despite the vast amount of research conducted on miRNAs in recent years, it is still necessary to increase and further strengthen studies on miRNAs and their targets to promote a better understanding on B cell development and as a result, construct more effective treatments against B cell disease.